Analisis Penetapan Harga Air di Subak Dangin Yeh Desa Giri Emas, Kecamatan Sawan, Kabupaten Buleleng - KADEK YARDI MAHADIKARA; I MADE SUDARMA; A.A. AYU WULANDIRA SAWITRI DJELANTIK (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Analysis of the Determination of Water Prices in Subak Dangin Yeh Giri EmasVillage, Sawan District, Buleleng RegencySubak Dangin Yeh is one of the subaks which describes the decrease in the availabilityof surface water. The application of conventional rice planting systems along with thedecreasing availability of water causes the use of water to be effective and efficient.Therefore this research becomes important to do. This research was conducted fromJanuary to April 2018 with the aim to find out the subak fees charged to farmers, thevalue of water that farmers use in achieving maximum chargeprofits and water pricesthat reflect the value of sustainable water use. The scope of this research is thedetermination of the water price used by farmers with quantitative calculation methods.The data were obtained through library research, direct observation, and in-depthinterviews. The population of this study was all subak members with a sample of 50respondents and determined by the Simple Random Sampling method. Subak feescharged to farmers amounting to Rp.760,000.00 / land / year. Based on VMP analysis,the value of water used by farmers in achieving maximum profits was Rp. 379,932.43 /ha / planting season. The price of water that reflects the value of sustainable water usefor groundwater irrigation was Rp.4,693.64 / m3 which consists of a full supply cost ofRp. 160.92 /m3, opportunity costs of Rp. 4,199.14/ m3, and a depletion premium ofRp.333,59 / m3. This price must be paid by farmers in an effort to maintain waterresources to remain sustainable in the future.